(untitled) (Journal of Management and Social Sciences, 2017)
Abstract The paper examines the impact of import and export on economic growth in Nigeria using Vector Autoregressive (VARs) technique through various types of structural analysis of Granger causality tests, impulse response functions, and forecast error variance decompositions to examine the dynamic effects of various shocks on macroeconomic variables. The results of VAR show that the predominant sources of Nigeria economic growth variation are due largely to â€œown shocksâ€ and import-export trade innovations. While Johansen Cointegration results showed that there is a stable, long- run relationship between import-export and economic growth, but the magnitude is minimal. In conclusion, the study agreed that government should always embark on policies that will encourage exports with proper implementation of import control measures. Â Keywords Import, export, economic growth, exchange rate, inflation rate